A common diagnosis in an uncommon age: acute neonatal parotitis case report - Inês Gameiro; Catarina Leuzinger-Dias; Margarida Camacho-Sampaio; Henrique Donato; Ana T. Gil (Publicaciones Permanyer, 2023)
Acute neonatal parotitis is a rare disease, usually with a clinical diagnosis. Parotid swelling and other inflammatory signs are essential characteristics. Purulent discharge of Stensen's duct is pathognomonic of suppurative parotitis. Staphylococcus aureus is the most common pathogen, although other organisms may also be involved. We describe the case of a 10-day-old term newborn who presented with subtle preauricular swelling and erythema. In this case, the ultrasound was essential since obvious inflammatory signs and purulent drainage only occurred later, and there were no known risk factors. No microorganism was isolated since it was not feasible to collect an uncontaminated sample. Empiric antimicrobial therapy was initiated, with consequent clinical improvement. This condition should be considered in the differential diagnosis of parotid region swelling. Early suspicion, diagnosis and appropriate combined antibiotics are essential for a rapid and complicationsfree recovery.